TASTY trial: protocol for a study on the triad of nutrition, intestinal microbiota and rheumatoid arthritis - Charneca, S (2025)
Background The gut microbiota has been implicated in the onset and progression of Rheumatoid Arthritis (RA). It has been proposed that gut dysbiosis impairs gut barrier function, leading to alterations in mucosal integrity and immunity. This disruption allows bacterial translocation, contributing to the perpetuation of the inflammatory process. Since diet is recognised as a key environmental factor influencing the gut microbiota, nutritional interventions targeting RA activity are currently being explored. This study aims to investigate whether a dietary intervention based on a typical Mediterranean Diet enriched with fermented foods (MedDiet +) can impact the gut microbiota, intestinal permeability, and RA-related outcomes. Methods One hundred RA patients are being recruited at Unidade Local de Saúde (ULS) Santa Maria in Lisbon, Portugal, and randomly assigned to either the intervention (MedDiet +) or the control group. The 12-week nutritional intervention includes a personalised dietary plan following the MedDiet + pattern, along with educational resources, food basket deliveries, and clinical culinary workshops, all developed and monitored weekly by registered dietitians. The control group receives standardised general healthy diet recommendations at baseline. The intervention’s effects will be assessed by evaluating disease activity, functional status, quality of life, intestinal permeability, endotoxemia, inflammatory biomarkers, intestinal and oral microbiota, serum proteomics, and serum glycome profile characterisation. Discussion We anticipate obtaining integrative insights into the interplay between diet, the gut, and RA, while also exploring the underlying mechanisms driving these changes. This study, conducted by a multidisciplinary research team of registered dietitians, rheumatologists, biologists, and immunologists, aims to bridge the current gap between nutrition-related knowledge and RA. Trial registration Registered in ClinicalTrials.gov (NCT06758817; date of registry: January 6th 2025).